2021
DOI: 10.1200/jco.2021.39.6_suppl.26
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of BRCA1, BRCA2 (BRCA), and ATM mutations identified in matched tumor tissue and circulating tumor DNA (ctDNA) in men with metastatic castration-resistant prostate cancer (mCRPC) screened in the PROfound study.

Abstract: 26 Background: Not all mCRPC patients have available or sufficient tissue for multigene molecular testing. In the Phase 3 PROfound study, olaparib significantly improved radiographic progression-free survival compared with physician’s choice of abiraterone or enzalutamide in men with homologous recombination repair (HRR)-gene-mutated mCRPC (de Bono et al. N Engl J Med 2020). Overall, 31% of patients’ tissue samples failed molecular screening during the study, showing the need for additional testing methods to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…It has been shown that ctDNA can sufficiently identify all driver DNA alterations found in matched metastatic tissue in the majority of patients with mCRPC [ 156 ]. Data from the PROFOUND trial found a high concordance between tumor tissue and circulating tumor DNA (ctDNA), supporting the development of ctDNA testing as a minimally invasive method to identify patients with DDR-altered mCRPC [ 157 ]. In metastatic disease, ctDNA can identify somatic mutations, copy-number variations, and structural rearrangements that are predictive of response to therapies.…”
Section: Predictive Biomarkers and Potential Impact On Treatment Sequencementioning
confidence: 99%
“…It has been shown that ctDNA can sufficiently identify all driver DNA alterations found in matched metastatic tissue in the majority of patients with mCRPC [ 156 ]. Data from the PROFOUND trial found a high concordance between tumor tissue and circulating tumor DNA (ctDNA), supporting the development of ctDNA testing as a minimally invasive method to identify patients with DDR-altered mCRPC [ 157 ]. In metastatic disease, ctDNA can identify somatic mutations, copy-number variations, and structural rearrangements that are predictive of response to therapies.…”
Section: Predictive Biomarkers and Potential Impact On Treatment Sequencementioning
confidence: 99%
“…Eighty-one percent (503/619) of ctDNA samples tested yielded a result. High concordance between tumor tissues and ctDNA was found, with 81% positive percentage agreement and 92% negative percentage agreement [93]. Of the 181 patients in the BRCA/ATM cohort of the study who consented and provided a plasma sample for ctDNA testing, 42 (23.2%) samples failed analyses.…”
Section: Molecular Profiling Potential and Limitsmentioning
confidence: 90%
“…For instance, in the PROfound trial screening, 30% of biopsies were not suitable for DNA analysis [96]. High concordance between tumor tissues and ctDNA was found, with 81% positive percentage agreement and 92% negative percentage agreement [93]. Liquid biopsies may then be helpful.…”
Section: Parp Inhibitors In 2021mentioning
confidence: 99%
“…Another limitation for ctDNA analyses relates to the detection of larger genomic alterations. For example, durable responses to PARP inhibitors in prostate cancers are associated to homologous deletions of the BRCA2 gene [157], but the rate of concordance between tissue and blood based NGS is definitely low for the detection of deletion/rearrangement for BRCA2/1 and ATM (43%), in favor of the former [158]. This must be taken into account when choosing the analysis to be performed.…”
Section: Blood-based Toolsmentioning
confidence: 99%